Impact of community forest program in protection forest on livelihood outcomes: A case study of Lampung Province, Indonesia. (3rd April 2017) - Kaskoyo, Hari; Mohammed, AbrarJuhar; Inoue, Makoto
ABSTRACT: The global to local-level importance of Indonesian forests for the environment and development is now very well documented. However, how to govern these forests to achieve the diverse and, at times, conflicting interests is still an open question. Hutan Kemasyarakatan (HKm) is a community forest (CF) that is being implemented to contribute to local development while creating sufficient incentives for conserving the forest. Previous studies have demonstrated the potential of HKm to conserve forests. This study analyzed the changes in the five major types of capital for HKm farmers. The results indicated HKm to have contributed positively to the improvement of natural, physical, and human capital. In addition to its direct impact, HKm was also found to improve the financial capital of the farmers by avoiding patron–client relationships and side payments between the pre-HKm illegal encroacher farmers (now legal land cultivators) and government officers. Although the results support the possibility of HKm producing a win-win situation between forest conservation and rural development, its future applicability, especially with consideration of population growth and associated increase in demand for cultivation land, needs to be given due emphasis.